- 注册时间
- 2012-3-25
- 最后登录
- 1970-1-1
- 威望
- 星
- 金币
- 枚
- 贡献
- 分
- 经验
- 点
- 鲜花
- 朵
- 魅力
- 点
- 上传
- 次
- 下载
- 次
- 积分
- 1777
- 在线时间
- 小时
|
发表于 2014-1-22 17:37:54
|
显示全部楼层
\[ \begin{align*} \Gamma^2(N) &= \left( \int_0^{\infty}e^{-x}x^{N-1}\, \mathrm{d}x \right)^2 \\ &= \int_0^{\infty} \int_0^{\infty} e^{-u}u^{N-1} e^{-v}v^{N-1}\, \mathrm{d}u \, \mathrm{d}v \\ &= \int_0^1 \int_0^{\infty} e^{-x}(tx)^{N-1}((1-t)x)^{N-1}x\, \mathrm{d}x \, \mathrm{d}t \color{black}{\ \ \ \ (\ \mathrm{Set}\ u=tx, \, v=(1-t)x\ )} \\ &= \left(\int_0^{\infty}e^{-x} x^{2N-1} \, \mathrm{d}x \right) \cdot \left( \int_0^1 t^{N-1} (1-t)^{N-1}\, \mathrm{d}t \right) \\ &= \Gamma(2N) \left( \int_0^1 t^{N-1} \sum_{n=0}^{N-1}(-1)^n \binom{N-1}{n}t^n \, \mathrm{d}t \right) \\ &= \Gamma(2N) \left( \sum_{n=0}^{N-1} \int_0^1 (-1)^n \binom{N-1}{n}t^{N+n-1} \, \mathrm{d}t \right) \\ &= \Gamma(2N)\sum_{n=0}^{N-1}\frac{(-1)^n}{n+N}\binom{N-1}{n}\end{align*} \]
Any problem? |
评分
-
参与人数 1 | 威望 +6 |
金币 +8 |
贡献 +6 |
经验 +6 |
鲜花 +6 |
收起
理由
|
hujunhua
| + 6 |
+ 8 |
+ 6 |
+ 6 |
+ 6 |
没问题! 就是那个巧妙的变量代换有点突兀 |
查看全部评分
|